PREDIKSI TINGKAT KERUSAKAN BATANG ROTOR PADA MOTOR INDUKSI BERDASAR ANALISIS CIRI ARUS CATU DAN CIRI GETARANG - Nurhadi, Indra; Abidin, Zainal; Darmawan, Haris (Mesin, 2017)
Typically, mechanical vibration signature analysis is one of the essential steps in predictive maintenance activity for rotating machines. This paper discusses a study on the use of motor current signature analysis as a complement to the vibration signature analysis in identifying broken rotor bar in 3-phase induction motors. From literature study[5, 6, 7, 8, 9, 10, 11], it was summarized that the presence of rotor bar faults can be detected through the increase in (1x rpm ± Fs x p) side-bands amplitude of mechanical vibration. In addition, this type of fault is also signified by the increase in (1 ± 2s)Fl side-bands amplitude of motor current. Furthermore, the amplitude of the left side-band of supply current spectra can be used to estimate fault severity. To prove the validity of the theory and to study its feasibility for practical use, experimentation was conducted using a small 2-pole motor of ¼ hp, coupled with a generator. Spectral analysis performed on motor current and body vibration shows results as predicted by the theory.